Length-weight relationship and condition factor of an endemic Lagusia micracanthus Bleeker, 1860 in Rivers of the Maros Watershed - Muhammad Nur; M. Fadjar Rahardjo; Charles P.H Simanjuntak; Djumanto Djumanto; Krismono Krismono (Jurnal Iktiologi Indonesia, 2020)
Lagusia micracanthus is one of endemic freshwater fish in Sulawesi. It also has been locally consumed. The purpose of this research was to analyze length-weight relationship and condition factors of L. micracanthus in rivers of the Maros Watershed, South Sulawesi Province . The study was conducted in three rivers, namely Pattunuang River, Bantimurung River and Pucak River. The sampling was conducted monthly from May 2018 to April 2019. Fish samples were collected by an electric shocker (12 V and 9 A). A total of 1850 individual fishes with samples ranging from 31.58-127.79 mm in total length and 0.76-31.07 g in weight. The length-weight relationship was W = 0.00009L2.6241 (r = 0.95) in Pattunuang River, W = 0.0001L2.5237 (r = 0.94) in Bantimurung River, and W = 0.0001L2.4953 (r = 0.92) in Pucak River. The slope (b) values of L. micracanthus obtained a negative allometric growth pattern (b <3). The relative condition factors of L. micracanthus was fluctuated from 0.86 to 1.43 in Pattunuang River, 0.65 to 1.45 in Bantimurung River, and 0.55 to 1.26 in Pucak River. The condition factor increased towards the peak of the spawning season and decreased after the spawning period. The condition factor increased with the increasing of gonad maturity stage up to stage IV and decreased after spawned or stage V. Abstrak Lagusia micracanthus merupakan salah satu ikan endemik air tawar Sulawesi.Ikan ini telah lama dimanfaatkan masyarakat lokal sebagai ikan konsumsi. Penelitian ini bertujuan menganalisis hubungan panjang-bobot dan faktor kondisi L. micracanthus di sungai-sungai pada Daerah Aliran Sungai Maros, Provinsi Sulawesi Selatan. Penelitian dilakukan di tiga Sungai yaitu Sungai Pattunuang, Sungai Bantimurung dan Sungai Pucak. Pengambilan ikan contoh dilakukan setiap bulan dari Mei 2018 hingga April 2019. Penangkapan ikan contoh menggunakan alat tangkap electric shocker (12 V & 9 A). Total ikan yang tertangkap sebanyak 1850 ekor dengan panjang berkisar 31,58-127,79 mm dan bobot 0,76-31,07 g. Hasil penelitian menunjukkan, hubungan panjang bobot L. micracanthus di Sungai Pattunuang adalah W = 0,00009L2,6241 (r = 0,95), Sungai Bantimurung W= 0,0001L2,5237 (r = 0,94) dan Sungai Pucak W = 0,0001L2,4953 (r = 0,92). Berdasarkan nilai b yang diperoleh L. micracanthus tergolong ke dalam tipe pertumbuhan allometrik negatif (b < 3). Nilai faktor kondisi ikan pirik berfluktuasi. Di Sungai Pattunuang nilai faktor kondisi berkisar antara 0,55-1,26, di Sungai Bantimurung berkisar 0,65-1,45 dan di Sungai Pucak berkisar 0,55-1,26. Faktor kondisi meningkat menjelang puncak musim pemijahan dan menurun setelah masa pemijahan. Faktor kondisi meningkat seiring peningkatan tingkat kematangan gonad sampai pada TKG IV dan menurun setelah ikan berpijah atau pada TKG V.